If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7x + -4) = 21x + -12 Reorder the terms: (-4 + 7x) = 21x + -12 Remove parenthesis around (-4 + 7x) -4 + 7x = 21x + -12 Reorder the terms: -4 + 7x = -12 + 21x Solving -4 + 7x = -12 + 21x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-21x' to each side of the equation. -4 + 7x + -21x = -12 + 21x + -21x Combine like terms: 7x + -21x = -14x -4 + -14x = -12 + 21x + -21x Combine like terms: 21x + -21x = 0 -4 + -14x = -12 + 0 -4 + -14x = -12 Add '4' to each side of the equation. -4 + 4 + -14x = -12 + 4 Combine like terms: -4 + 4 = 0 0 + -14x = -12 + 4 -14x = -12 + 4 Combine like terms: -12 + 4 = -8 -14x = -8 Divide each side by '-14'. x = 0.5714285714 Simplifying x = 0.5714285714
| 4x-50=2x-34 | | 8x=-2x+7-4x | | (3x+22/7)+(x+11/4)=12 | | y=3x^3-14x^2+15x | | 4x-21=x-8 | | 3x^3-14x^2+15x=y | | 5x+7=28 | | 3(x+5)=-2(x-5) | | 4p-2(2-3p)=6(p-6)-36 | | -[8z-(14z+1)]=1+(5z+0) | | 0=x^2-4.75x+3 | | 10x^2+5-7x-6x^2-13x= | | 2*(4x-3)=3x-5 | | x^2-4.75-24=0 | | 6(x-6)-8(x+2)=-10 | | 6x-15=9+3x | | 13x+17y=19 | | 2x+10=6+4x | | -7(x+4)+4x+7=8x+6 | | 7/60=a | | 2x-16=-128 | | 1.4(x)=2x-3 | | 2/5*7/-6*-7=a | | .5(x)=2x-3 | | x+18=106 | | 2/5*7/-6*-7 | | -1(x)=2x-3 | | 1(x)=2x-3 | | 4/-6+2=-1 | | 3(x)=2x-3 | | 3(6x-4)-4(x+7)=6x-96+x | | 4(4x+1)=3x-4(6-x)8 |